Cattle farmers' perceptions of risk and risk management strategies: evidence from Northern Ethiopia. Issue 5 (4th May 2018) - Bishu, Kinfe G.; O'Reilly, Seamus; Lahiff, Edward; Steiner, Bodo
Abstract : This study analyzes cattle farmers' perceptions of risk and risk management strategies in Tigray, Northern Ethiopia. We use survey data from a sample of 356 farmers based on multistage random sampling. Factor analysis is employed to classify scores of risk and management strategies, and multiple regression is then used to investigate the relationship between scores and farmers' characteristics. The results demonstrate that shortage of family labor, high price of fodder, and limited farm income were perceived as the most important risks. Use of veterinary services, parasite control, and loan utilization were perceived as the most important strategies for managing risks. Livestock disease and labor shortage were perceived as less of a risk by farmers who adopted the practice of zero grazing compared to other farmers, pointing to the potential of this practice for risk reduction. We find strong evidence that farmers engage in multiple risk management practices in order to reduce losses from cattle morbidity and mortality. The results suggest that government strategies that aim at reducing farmers' risk need to be tailored to specific farm and farmer characteristics. Findings from this study have potentially important policy implications for risk management strategies in developing countries.